2020
DOI: 10.1021/acs.orglett.0c02835
|View full text |Cite
|
Sign up to set email alerts
|

Silver-Catalyzed Cascade Cyclization Reaction of Isocyanides with Sulfoxonium Ylides: Synthesis of 3-Aminofurans and 4-Aminoquinolines

Abstract: A silver-catalyzed cascade cyclization reaction of isocyanides with sulfoxonium ylides has been developed for the first time. This reaction provides a new and efficient method for the construction of highly functionalized 3-aminofurans and 4-aminoquinolines from readily available starting materials in a single step.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 94 publications
(29 reference statements)
0
17
0
Order By: Relevance
“…Adjusting the ratio of 1 d and 2 a by increasing the amounts of 1 d had a beneficial influence on the reaction, as demonstrated that 83 % yield of product 3 d was achieved when 3.0 equiv. of TFISY 1 d was employed (Table 1, entries [14][15][16]. Surprisingly, the reaction yield was sharply improved to 97 % in the absence of base, suggesting the reaction proceeded smoothly only under heating conditions (Table 1, entry 17).…”
Section: Resultsmentioning
confidence: 99%
“…Adjusting the ratio of 1 d and 2 a by increasing the amounts of 1 d had a beneficial influence on the reaction, as demonstrated that 83 % yield of product 3 d was achieved when 3.0 equiv. of TFISY 1 d was employed (Table 1, entries [14][15][16]. Surprisingly, the reaction yield was sharply improved to 97 % in the absence of base, suggesting the reaction proceeded smoothly only under heating conditions (Table 1, entry 17).…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that Ph- and t Bu-containing imidoyl sulfoxonium ylides failed to provide the isoquinolinone products, which highlighted the importance of the CF 3 group in the success of this reaction ( 3y , 3z ). 14 In the case of Ph-imidoyl sulfoxonium, the hydrolysis of imidoyl sulfoxonium was observed and 7-methyl-3-phenyl-isocoumarin was isolated as the major product. 11d…”
Section: Resultsmentioning
confidence: 99%
“…In consideration of the high reactivity of TFISYs and the precedent work about the silver-catalyzed reaction of isocyanides with sulfoxonium ylides, 64 a heating-induced desulfurization annulation of TFISYs and isothiocyanates for the construction of biologically valuable 2-trifluoromethyl-4-aminoquinolines was presented by Wu, Chen and co-workers (Scheme 51). 65 The simple transformation was performed under catalyst- and additive-free conditions, which had many advantages of easy operation, insensitivity to air and moisture, high efficiency and scalibility.…”
Section: Synthesis Of Cf3-containing Heterocycles From Cf3-imidoyl Su...mentioning
confidence: 99%